Role of Courts in Ensuring Water Justice in India: Brasília Declaration on Water Justice and Beyond - Divakara Naik, Gayathri (Christ University Law Journal, 2022)
Water being a scarce resource, questions of its allocation and distribution, coupled with concerns of its depletion have troubled policy makers, legislators, and judges alike. While, over the years there has been significant development on the discussion surrounding the rights-duty paradigm of water resources, by establishing the obligation of states, discussion surrounding a certain value-based approach to guide the minds of important stakeholders in creating and enforcing policy has gained far less traction comparatively. It is in this context that this paper explores an alternative justice-based approach to water, drawing from the works of Amartya Sen on capabilities and more so the Brasilia Declaration of Judges on water justice and the various principles. This paper explores how judges can incorporate such an approach through their judgements. The paper also attempts to shift the focus from the hitherto considerations of an anthropocentric and economic nature that have governed water policy and adjudication, and further elaborates upon water as inherently a public good and an environmental necessity and the need for bolstering water management techniques on these grounds.